A Study of Molecular Subtypes of Carcinoma Breast by Immunohistochemistry at Tertiary Care Center, Jaipur - Arpita, Jindal; Priyanka, Gothwal; Ranjana, Solanki (Asian Pacific Journal of Cancer Biology, 2022)
Introduction: Breast cancer is one of the most common malignant tumors and one of the leading causes of cancer related death amongst females worldwide. The clinical significance of molecular classification of carcinoma breast remains to be established. Molecular subtyping using immunohistochemistry can provide additional prognostic and predictive information. Aim and objectives: To identify morphological variants of carcinoma breast and to determine various proportions of molecular subtypes of carcinoma breast by immunohistochemistry. Materials and Methods: A descriptive type of observational study was done at SMS Medical College, Jaipur. 65 Modified Radical Mastectomy specimens received in the department were included in the study. The surgical specimens were then evaluated histopathologically and immunohistochemically for ER, PR, HER2/neu, and Ki67 markers. Results: Out of 65 breast carcinoma cases the most common histological type encountered in our study was Invasive ductal carcinoma of no special type (NST) (83.09%) followed by medullary carcinoma (4.63%) and invasive lobular carcinoma (3.09%) and a single case each of tubular, cribriform, metaplastic, lymphoepithelioma like carcinoma, carcinoma with apocrine differentiation and oncocytic carcinoma. The cases were further classified into molecular subtypes using protein expression patterns in IHC. The proportion of tumors found were Luminal A (32.31%), Luminal B (18.46%), HER2/neu overexpressed (13.84%), and Triple-negative (35.39%). Conclusion: The most common molecular subtype found in our study was Triple negative. The use of IHC markers in the clinical setting could determine the prognosis and benefit the patients with targeted therapies.